FACTORS AFFECTING SAVING IN NATIONAL SAVINGS FUND OF THE SELF-EMPLOYMENT IN MUANG KRABI DISTRICT KRABI PROVICE - อ่อนจันทร์, ปิติพันธุ์; ศรีสุขใส, พิทักษ์ (RMUTT Global Business and Economics Review, 2017)
The Objectives were to study 1) the saving behavior of the self-employment 2) factors affecting saving decision in National Savings Fund (NSF) and 3) factors affecting the amount of saving in NSF. This study collected data using the questionnaire to survey the self-employment, included 400 subjects. The statistics used for analyzing the data were percentage to describe the savings behavior, binary logistic regression equation to explain the factors affecting savings decision in NSF, and multiple regression equation to explain the factors affecting the amount of savings in the NSF. The findings indicated that the average saving to income ratio was 19.23 percent. Most of the respondents saved their money through deposits at the banks, and they had only one channel for savings. About 63.0 percent of respondents did not know about the information of the NSF. Most of the samples saving in NSF planned to save 500 baht per month and the proportion of farmer was larger than others. In addition, the saving amount per month affected the saving decision and the money saved in NSF at the 0.05 significance level. In fact, the increase of one percent in saving amount per month leads to 0.029 percent change in the amount of saving in the fund. The income per month and the expenditures per month affected the amount of saving in NSF changed to 0.018 and -0.012 percent, respectively. The liabilities, motorcycle ownership, car ownership and size of land holding also affected the saving decision in NSF, but did not affect the amount of saving in the fund.